How digital branding enhances digital trust: a case study of three msmes in Medan - Miftah El Fikri; Danny Ajar Baskoro; Muhammad Nasir (Economic: Journal Economic and Business, 2026)
The rapid growth of digital technology has transformed how Micro, Small, and Medium Enterprises (MSMEs) build relationships with consumers through social media. This study examines the influence of Social Media Marketing on Digital Brand Trust through the mediating roles of Content Marketing and Digital Trust among three MSMEs in Medan: Miricare Oil, Syakir Collection, and Cemilan Kanaya. A quantitative approach was employed using a survey of 252 respondents selected through purposive sampling. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS. The findings reveal that Social Media Marketing has a positive and significant effect on Content Marketing, Digital Trust, and Digital Brand Trust. Digital Trust emerged as the strongest predictor of Digital Brand Trust, highlighting the importance of security, credibility, and reliability in digital interactions. Content Marketing significantly enhances Digital Brand Trust but does not directly influence Digital Trust. Furthermore, both Content Marketing and Digital Trust serve as significant mediating variables in strengthening the relationship between Social Media Marketing and Digital Brand Trust. These findings provide practical insights for MSMEs in developing effective digital marketing strategies that prioritize trust-building to improve brand competitiveness and long-term consumer relationships in the digital marketplace.